Mind the "gap": a comparison of the weekly training loads of English Premier League academy soccer players in under 23, under 18 and under 16 age-groups - Taylor, J. M.; Madden, J. L.; Hunter, F.; Thorne B. J.; McLaren, S. J. (Journal of Science in Sport and Exercise, 2023)
Purpose: The transition into full-time training represents a key period in the development of young soccer players. Here we compared the weekly training loads (matches, field-, and resistance-training) of English Premier-League Academy soccer players from under-16 (U16), under-18 (U18) and under-23 (U23) age-groups during a training meso-cycle. Methods: Forty players (U16 n = 13, U18 n = 15 and U23 n = 12) were monitored using global navigation satellite systems and differential ratings of perceived exertion (dRPE). External load metrics were total distance, high-speed running distance, [absolute: = 19.8 km/h, relative: = 87% of 30-15 final-velocity (vIFT)], sprint distance (absolute: = 25.2 km/h, relative: = 80% maximal sprint speed), and dynamic stress load. Internal load metrics were dRPE training loads. Results: Other than relative sprint distance, overall weekly external training loads were substantially greater for U18s and U23s when compared with U16s [effect size range: 1.09-1.99 (moderate to large); ± 90% confidence limits ~ 0.45]. When compared with U16s, overall internal loads were substantially greater for U18s [0.69-0.95 (moderate); ± ~ 0.40], but not U23s. Differences in weekly training loads between U18s and U23s were inconclusive. Conclusions: Substantial differences in training loads between elite U16 players and their older counterparts, indicates the need for planned increases in training loads in anticipation of the transition into full-time training.